The Impact of Language Switching Frequency on Attentional and Executive Functioning in Proficient Bilingual Adults - Barbu, Cristina; Orban, Sarah; Gillet, Sophie; Poncelet, Martine (Psychologica Belgica, 2018)
Bilingual advantages in executive functions are well documented (see Bialystok, 2009; Dong & Li, 2015, for a review), but the specific aspects of bilingualism that underlie these advantages are unclear. The few studies conducted up until now on this subject (e.g., Hartanto & Yang, 2016; Prior & Gollan, 2011; Verreyt, Woumans, Vandelanotte, Szmalec, & Duyck, 2016) have suggested that the frequency of language switching may partially mediate this advantage. We further investigate the impact of oral language-switching frequency on the development of alerting, response inhibition and cognitive flexibility skills in proficient bilinguals. Two groups of proficient bilingual adults (21 low-frequency language switchers and 21 high-frequency language switchers), matched for age, gender, second-language proficiency and socio-cultural status, participated in the study. Tasks assessing alerting, response inhibition and cognitive flexibility were administered. Our results revealed that high-frequency language switchers responded more quickly in the task assessing cognitive flexibility. No group effect was found on the tasks assessing alerting and response inhibition. These results suggest that language-switching frequency is likely an underlying factor in the enhanced cognitive flexibility of proficient bilinguals.